211k views
1 vote
Solve forx.
(2x - 1) (5x+3) = 0

1 Answer

6 votes


\huge\text{Hey there!}


\large\textsf{(2x - 1)(5x + 3) = 0}\\\rightarrow\large\textsf{10x}\mathsf{^2}\large\textsf{ + x - 3 = 0}


\huge\text{FACTOR the LEFT SIDE of the equation}


\large\textsf{(5x + 3)(2x - 1) = 0}


\huge\text{SET the FACTORS to equal to 0}


\large\textsf{5x + 3 = 0 or 2x - 1 = 0}


\huge\text{SIMPLIFY \& YOU HAVE YOUR RESULT}\\\\\huge\text{to your question if you solved correctly.}


\boxed{\boxed{\huge\text{Answer: \boxed{\mathsf{x = - (3)/(5)\ or \ x = (1)/(2)}}}}}\huge\checkmark


\huge\text{Good luck on your assignment \& enjoy your day!}

~
\frak{Amphitrite1040:)}

User Ayoub
by
4.7k points